UTILIZAÇÃO DO STOP-BANG PARA INVESTIGAÇÃO DA SÍNDROME DA APNEIA OBSTRUTIVA DO SONO: REVISÃO DE LITERATURA - Thamires Bessa (UniEVANGÉLICA, 2018)
Objective: The objective of the present study was to conduct a literature review on the use of Snoring, Tiredness, Observerd apnea, high blood Pressure, Body mass index, Age, Neck circumference, and Gender (STOP-Bang) as a tool to identify the risk of Obstructive Sleep Apnea Syndrome (OSAS). Methods: This was a literature review, based on the Scielo, MedLine and Cochrane databases. We included articles in English and Portuguese, in the period of 2010 and 2017, carried out with human beings with OSAS who used STOP-Bang for diagnostic investigation Results: Twenty studies were included with individuals diagnosed with OSAS. STOP-Bang is a usefull and simple instrument for screening and categorizing the severity of OSAS, presenting good sensitivity and specificity when compared to the gold standard examination, Polysomnography. A high STOP-Bang score, greater than or equal to 5 to 8 points, indicates a high probability of moderate to severe OSAS. Conclusions: STOP-Bang is shown as a practical and useful instrument for the identification of OSA risk, presenting good sensitivity and specificity when related to the gold standard examination.